2011
DOI: 10.3892/ijo.2011.1160
|View full text |Cite
|
Sign up to set email alerts
|

Oligodendroglioma cells shed microvesicles which contain TRAIL as well as molecular chaperones and induce cell death in astrocytes

Abstract: Abstract. Microvesicles (MVs) shed from G26/24 oligodendroglioma cells were previously reported to cause a reproducible, dose-dependent, inhibitory effect on neurite outgrowth, and eventually neuronal apoptosis, when added to primary cultures of rat cortical neurons. These effects were reduced but not abolished by functional monoclonal antibodies against Fas-L. In order to investigate whether MVs contain other factors able to induce cell death, we tested them for TRAIL and found clear evidence of its presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 16 publications
1
36
0
Order By: Relevance
“…Parallel studies showed that the mRNA for EGFRvIII is also present in EMVs from mutant-positive tumor cells and can be detected in serum EMVs from patients who harbor the corresponding mutation in their tumors, thereby providing a biomarker for genetic status of the tumors (Skog et al, 2008). Others have shown that oligodendroglioma cells send out EMVs containing the apoptotic protein, TRAIL, which leads to death of normal astrocytes and neurons (Lo Cicero et al, 2011). …”
Section: Functions Of Emvs In the Nervous Systemmentioning
confidence: 99%
“…Parallel studies showed that the mRNA for EGFRvIII is also present in EMVs from mutant-positive tumor cells and can be detected in serum EMVs from patients who harbor the corresponding mutation in their tumors, thereby providing a biomarker for genetic status of the tumors (Skog et al, 2008). Others have shown that oligodendroglioma cells send out EMVs containing the apoptotic protein, TRAIL, which leads to death of normal astrocytes and neurons (Lo Cicero et al, 2011). …”
Section: Functions Of Emvs In the Nervous Systemmentioning
confidence: 99%
“…Other articles of interest have shown that various brain tumor cell EVs (from GBMs, oligodendroglioma cells, and medulloblastoma cells) have activities and impacts on recipient cells that range from transformation of those cells53 to induction of apoptosis,54 along with growth promotion and migratory-driving activities 55. That paper55 again showed the immune dichotomy of medulloblastoma exosomes in both immunosuppressive and immunostimulatory functions and identified almost 150 proteins in proteomic analyses.…”
Section: Extracellular Vesicles In Neuro-oncology: Biology and Potentmentioning
confidence: 92%
“…Thus, new therapeutic approaches are urgently needed. Tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) has great promise as an anticancer drug because of its potent proapoptotic effects on cancer cell and negligible toxicity on healthy cells, including human astrocytes [2]. Glioma stem cells, a self-renewing and tumorigenic subpopulation of glioma cells, have been implicated in the treatment resistance of glioblastoma (GBM) and could therefore be responsible for resistance to TRAIL-induced cell death observed in gliomas [3].…”
Section: Introductionmentioning
confidence: 99%